MASALAH SOSIAL DALAM DUNIA BISNIS DI INDONESIA : SEBUAH PERSPEKTIF AKUNTANSI SOSIAL - Azizul Kholis (Media Riset Akuntansi, Auditing & Informasi, 2002)
The Collapse of Indonesian corporation, to some extent, due to its internal entity environment. The lack of social concern, showed by extent of social disclosure through financial report by entities is a root of the problem. So far the orientation of financial report only to shareholders. To create an effective communication between business and society the role of financial accounting is important Social Accounting argues that the going concern of a company cannot be separated from sodety. The paper argues that in Indonesian business needs social reporting to develop social stability and the healthy of economy and investment.Keywords: Social problem, Social environment, Social accounting, Social disclosure.